The effect of Islamic revolution and war on income inequality in Iran - Mohammad Reza Farzanegan; Mohammad Ali Kadivar (Empirical Economics, 2023)
Existing research has pointed to the decreasing effect of revolutions and wars on income inequality. It is unclear whether this reduction is the result of ongoing changes before revolutions and wars or if the results are standalone effects. In this study, we focus on the case of the Iranian Revolution of 1978–1979 and the subsequent Iran–Iraq war from 1980 to 1988. We use the synthetic control method to study the effect of revolution and war on changes in income inequality levels. Had there been no revolution and war in Iran, how would income inequality have developed? Utilizing the synthetic control method, we create a counterfactual Iran that reproduces the socioeconomic characteristics of Iran before the Islamic revolution. Then, we compare the income inequality of the counterfactual Iran without the revolution and war to the factual Iran under a new political regime for the period of 1970–1988. Our results, based on two different indicators of Iran's Gini index, show a significant effect of the revolution and war on reducing income inequality. Over the entire 1979–1988 period, on average and per year, the Gini index of Iran was reduced by approximately three standard deviations of the index. The main findings are robust to a series of tests, including placebo tests.
Keywords: 330; Income inequality; War; Revolution; Iran; Synthetic control; Counterfactual